2019
DOI: 10.2196/13664
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Patient Loneliness With Artificial Agents: Design Insights From Evolutionary Neuropsychiatry

Abstract: Loneliness is a growing public health issue that substantially increases the risk of morbidity and mortality. Artificial agents, such as robots, embodied conversational agents, and chatbots, present an innovation in care delivery and have been shown to reduce patient loneliness by providing social support. However, similar to doctor and patient relationships, the quality of a patient’s relationship with an artificial agent can impact support effectiveness as well as care engagement. Incorporating mammalian att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Artificial agents, such as robots, embodied conversational agents and chatbots, have been shown to reduce NCCD loneliness by providing social support (Loveys et al, 2019). A number of digital solutions are available to help coordinate and connect a network of caregivers and services.…”
Section: Enablers To Enable a Public Health Approachmentioning
confidence: 99%
“…Artificial agents, such as robots, embodied conversational agents and chatbots, have been shown to reduce NCCD loneliness by providing social support (Loveys et al, 2019). A number of digital solutions are available to help coordinate and connect a network of caregivers and services.…”
Section: Enablers To Enable a Public Health Approachmentioning
confidence: 99%
“…In other words, loneliness may be closely related to the status of social adaptability among adolescents. Moreover, previous studies also found that AI agents can help patients reduce loneliness by providing social support [27]. Impulsivity, an important personality trait, is also an effective predictor of social adaptability (Moschetta, Valente, and K., 2013).…”
Section: Personality Factors and Learner-related Factors That Related...mentioning
confidence: 96%
“…In healthcare, humanoid robots are designed and often used by individuals at home or at healthcare centres for improving their medical conditions (Choudhury et al, 2018). In various areas of therapy, for example, the use of AI technologies is a burgeoning area that has seen important developments over the last decade (Dautenhahn, 2003;D'Alfonso et al, 2017;Luxton, 2014;Guerrero et al, 2016;Blusi and Nieves, 2019;Loveys et al, 2019). AI in the form of SIAs is already under study as a therapy, particularly for children with autism and children with Asperger's syndrome.…”
Section: Sias In Healthcare and Educationmentioning
confidence: 99%
“…Furthermore, in healthcare, for example, SIAs could be designed to reduce loneliness in patients (Loveys et al, 2019). Furthermore, these systems can be built to support young and old patients psychologically through the immediate recommendation of measures in addressing their mental health, as well as assist their therapists in diagnosis (D'Alfonso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%